Analysis of the Influence of Brand Awareness, Brand Trust and Brand Experience on Purchasing Decisions in the Shoope Marketplace in Muhammadiyah University Students Faculty of Economics and Bussiness 2021-2023 - Ekasari, Widia Aulia; Nursaidah, Nursaidah; Rusdiyanto, Rusdiyanto (Westscience Press, 2025)
The development of tecchnology and the internet has changed consumer behavior in shopping, especially through the Shopee marketplace. This has driven changes in people’s behavior patterns. As one of the largest marketplace in Indonesia, Shopee offers various conveniences in online transactions, a variety of product choices, and attractive promotions. This study aims the analyze brand awareness, brand trust and brand experience on purchasing decisions in the Shopee marketplace among student of the Muhammadiyah University of Jember Faculty of Economics and Business clas of 2021-2023. This study uses an associative quantitative method. The population used was student of the Muhammadiyah University of Jember Faculty of Economics and Business class of 2021-2023. The sample approach included purposive sampling of 99 students. The study's findings revealed that the variables brand awareness, brand trust, and brand experience had a positive and substantial effect on purchase decisions made through the Shopee marketplace with a result of 53.9%, with the remaining 46.1% influenced by other factors.